A REVIEW OF THEORIES AND COPING STRATEGIES FOR CROSS-CULTURAL ADAPTATION OF INTERNATIONAL STUDENTS - Chen , Zhifang; Yin, Julia Tan Yin; Afip, Liyana Ahmad (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
With the development of globalization and the internationalization of education, an increasing number of international students are emerging, bringing with challenges in cross-cultural adaptation. This narrative literature review aims to examine the theoretical foundations of cross-cultural adaptation for international students and to identify a classification and indicators of coping strategies for international students’ cross-cultural adaptation, with the goal of helping them achieve more effective cross-cultural adaptation. Through the analysis of existing literature, it was found that research focuses primarily on the United States and other developed Western countries, while developing countries like China lack localized cross-cultural adaptation theories. The focus is primarily on high school or undergraduate education, with insufficient attention paid to international students in higher vocational colleges. Furthermore, there is a disconnect between practical approaches, and the systematic and targeted nature of coping strategies remains to be improved. Future research should strengthen the development of localized theories in developing countries like China, as well as the focus on international students in higher vocational colleges. This study contributes by proposing a localized analytical framework and promoting high-quality development of international education in various countries.